A cognitive account of agentive awareness. (14th November 2017) - Mylopoulos, Myrto
Abstract : Agentive awareness is one's awareness of oneself as presently acting. Dominant accounts in cognitive science consider agentive awareness to be grounded in the states and processes underlying sensorimotor control. In this paper, I raise concerns for this approach and develop an alternative. Broadly, in the approach I defend, one is agentively aware in the virtue of intending to act. I further argue that agentive awareness is not constituted by intentions themselves but rather first‐personal thoughts that are formed on the basis of them. I develop this proposal, highlight some of its theoretical advantages, and show how it successfully meets various challenges.